(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Emotional maturity is about the ability to understand and manage emotions. An emotionally mature person has reached (and continues to work at reaching) a level of Self-Understanding with regard to their thoughts and behaviors and then decides how to best approach and cope with situations that might otherwise be trying or challenging. Being emotionally mature can help to reach successful resolutions to problems, as well as keep problems from overwhelming you. In this paper, The Vineland Social Maturity Scale is used which is a psychometric assessment instrument designed to help in the assessment of social competence. It was developed by the American psychologist Edgar Arnold Doll and published in 1940.He published a manual for it in 1953. Raggio, DJ; Massingale, TW (1990). "Comparability of the Vineland Social Maturity Scale and the Vineland Adaptive Behavior Scale–survey form with infants evaluated for developmental delay". Perceptual and Motor Skills. 71, Doll named it after the Vineland Training School for the Mentally Retarded, where he developed it. In this paper, Using formalized and established hypothesis testing procedures means that have to carefully consider and report your research variables, predictions, data collection and testing methods before coming to a conclusion. Quantitative data analysis method is used with Descriptive statistics and inferential statistics include measures of averages and variability. It can also used graphs, scatter plots and frequency tables to visualize data and check for any trends or outliers. Emotionally mature people don’t have a false sense of self that is ego-based and deluded. But they do have optimism in their own ability to use effort and patience as a way to establish the belief that they are equipped to deal with whatever life may through their way in Nadia district.